PTSD in Children and Adolescents in the Educational Context. A Conceptual Approach - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Tsagri, Angeliki; Tseremegklis, Chrysostomos; Tsogka, Danai; Lourida, Konstantina; Mitroyanni, Evangelia; Drongitis, Anastasios (Technium Social Sciences Journal, 2024)
This paper explores the multifaceted aspects of Post-Traumatic Stress Disorder (PTSD) in children and adolescents within educational contexts. It investigates the complexity of diagnosing PTSD in this demographic, recognizing the role of cognitive function, expression barriers, and parental influence. Considering the diverse and unique presentations of PTSD symptoms in children, the study highlights the challenges in identifying and treating PTSD among school-age children and adolescents, especially among highly vulnerable populations such as refugees. Through an extensive review of existing literature, the paper compares and contrasts the criteria from DSM-5 and ICD-11 for PTSD diagnosis and evaluates the efficacy of treatment options such as EMDR, CBT, and school-based interventions. The impact of PTSD on academic performance and social integration is emphasized, underlining the implications for educators, mental health professionals, and policy makers. Furthermore, the study calls attention to the co-occurrence of PTSD with other mental health conditions and the significant effects beyond educational achievement, including developmental, social, and cognitive domains. Drawing on current research, it advocates for integrated intervention strategies that promote socio-emotional learning, and underscores the importance of a secure, supportive educational environment.